Top Income Shares and Mortality: Evidence from Advanced Countries - Böckerman, Petri (Journal of Income Distribution®, 2015)
This article examines the effect of top income shares on crude death and infant mortality rates. We use balanced panel data that covers nine advanced countries over the period 1952-1998. Top income shares are measured as the shares of pre-tax income going to the richest 0.1 per cent, 1 per cent, and 10 per cent of the population. The main finding is that there is no overall relationship between top income shares and mortality measures. We also estimate separate effects on both female and male mortality rates. If anything, these estimates suggest that the male death rate is negatively correlated with inequality.